Wojna w Sierra Leone – z dziećmi w roli głównej - Janiszewska, Karolina (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The use of children in armed conflicts is one of the most serious problems of the modern world. As shown in reality, there is a real need to guarantee the inviolability of minors. This problem is still a major challenge. Its importance is illustrated on the example of the civil war in Sierra Leone. Analysis of memories of child soldiers and the people they recruited confirms that the rights of children, which will shape the world in the future, are brutally violated”.